Friars, Soldiers, and Reformers Hispanic Arizona and the Sonora Mission Frontier, 1767-1856 - Kessell, John L. (University of Arizona Press, 2016)
The Franciscan mission San José de Tumacácori and the perennially undermanned presidio Tubac become John L. Kessell's windows on the Arizona-Sonora frontier in this colorful documentary history. His fascinating view extends from the Jesuit expulsion to the coming of the U.S. Army. Kessell provides exciting accounts of the explorations of Francisco Garcés, de Anza's expeditions, and the Yuma massacre. Drawing from widely scattered archival materials, he vividly describes the epic struggle between Bishop Reyes and Father President Barbastro, the missionary scandals of 1815-18, and the bloody victory of Mexican civilian volunteers over Apaches in Arivaipa Canyon in 1832. Numerous missionaries, presidials, and bureaucrats-nameless in histories until now-emerge as living, swearing, praying, individuals. This authoritative chronicle offers an engrossing picture of the continually threatened mission frontier. Reformers championing civil rights for mission Indians time and again challenged the friars' "tight-fisted paternalistic control" over their wards. Expansionists repeatedly saw their plans dashed by Indian raids, uncooperative military officials, or lack of financial support. Friars, Soldiers, and Reformers brings into sharp focus the long, blurry period between Jesuit Sonora and Territorial Arizona.